Stylistic Features as Meaning-Making Resources in Selected Children’s Storybooks by Julia Donaldson - Christiani Velma Jessica Dame; Abd Halim; Fitriyani Bakri; Nur Mutmainnna Halim (Seltics Journal: Scope of English Language Teaching Literature and Linguistics, 2026)
Children’s storybooks employ carefully crafted linguistic patterns that not only entertain young readers but also function as important resources for meaning-making, engagement, and early language development. This study investigates stylistic features as meaning-making resources in selected children’s storybooks written by Julia Donaldson, namely The Gruffalo, Room on the Broom, and The Snail and the Whale. The study aims to examine the dominant stylistic features used in the selected texts and explore how these features function in constructing meaning for young readers. Employing a qualitative descriptive-analytic design, this research applies the stylistic framework of Leech and Short alongside Halliday’s Systemic Functional Linguistics (SFL). The analysis focuses on five stylistic categories: lexical, grammatical, phonological, graphological, and figurative features. The findings reveal that phonological features, particularly rhyme, rhythm, alliteration, and sound repetition, are the most dominant stylistic resources across the selected storybooks. These features function simultaneously as ideational resources that foreground semantic relationships, interpersonal resources that establish expressive and interactional dimensions within the narratives, and textual resources that organize narrative flow and coherence. Viewed through Halliday’s meta-functional framework, these stylistic patterns contribute to multiple layers of meaning construction within the selected storybooks. The study further demonstrates that stylistic choices in children’s storybooks are purposefully adapted to the cognitive and linguistic capacities of young readers, making narratives more accessible, memorable, and emotionally engaging. This study contributes to stylistics and children’s literature studies by highlighting how linguistic features function not merely as aesthetic devices, but as meaningful resources that support narrative construction and early literacy development.